2001
DOI: 10.1128/jcm.39.4.1630-1632.2001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microsporidia in Travelers with Diarrhea

Abstract: We examined stool specimens of 148 returning travelers from an outpatient department for tropical diseases for the appearence of microsporidia using light microscopy and PCR. Intestinal microsporidiosis was diagnosed for five patients by light microscopy and for nine patients by PCR. Some cases were diagnosed only by PCR, indicating that the true prevalence has to be determined by highly sensitive techniques, such as PCR.Diarrhea affects 20 to 70% of travelers in tropical or subtropical countries. Typically, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
48
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 20 publications
5
48
0
2
Order By: Relevance
“…In comparison to microscopy with Uvitex 2B fluorescent stain, the spiking experiments showed a 10-to 1,000-foldhigher sensitivity of the PCR compared to microscopy, comparable to data from other studies (27,32,42). A further advantage of PCR over microscopy, although not detected in our study, could be the detection of infections by two (or more) different species in one patient (31,32). One clinical sample was positive by PCR, while it was negative by microscopy.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In comparison to microscopy with Uvitex 2B fluorescent stain, the spiking experiments showed a 10-to 1,000-foldhigher sensitivity of the PCR compared to microscopy, comparable to data from other studies (27,32,42). A further advantage of PCR over microscopy, although not detected in our study, could be the detection of infections by two (or more) different species in one patient (31,32). One clinical sample was positive by PCR, while it was negative by microscopy.…”
Section: Discussionsupporting
confidence: 67%
“…Enterocytozoon bieneusi and the Encephalitozoon species E. intestinalis, E. hellem, and E. cuniculi have been described as opportunistic pathogens in human immunodeficiency virus (HIV)-infected patients and other immunocompromised patients such as transplant recipients (11,18,24,29,34,36). Infections with microsporidia in immunocompetent individuals such as travelers have also been described (31,35). In HIV-infected patients, E. bieneusi and E. intestinalis can cause a severe, persistent diarrhea, and the species have frequently been isolated from stool specimens (11,16,17,34,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of the positive samples contained E. intestinalis, and seven contained E. bieneusi, which are the most frequently microsporidian species detected in AIDS patients. Our data not only demonstrated the ability of microarrays to simultaneously detect multiple species but also further suggested that coinfection of microsporidia is not an uncommon event (24). However, it will be more interesting to investigate why this batch of archived samples had such a high incidence of dual infections.…”
Section: Discussionmentioning
confidence: 97%
“…The two other species of Encephalitozoon, E. cuniculi and E. hellem, are also known to cause disseminated infections including the urogenital, respiratory, and ocular organs. There are, however, two reports of enteric localization of E. cuniculi (2,5), and very recently, an E. hellem was recognized for the first time in stools of two immunocompetent travelers with diarrhea (6).…”
mentioning
confidence: 99%